PSVIII-31 Grass and legume hays for feedlot sheep: in vivo digestibility and in situ degradability. (7th December 2018) - Otoni, I; Ribeiro, K; Valadares, S; Silva, T; Silva, L; Silva, J; Pereira, O
Abstract: The objective of this study was to evaluate in vivo digestibility and in situ degradability of grass (Cynodon cvs. Jiggs and Tifton-85) and legume hays (Medicago sativa and Stylosanthes cv. Campo Grande), and nutrient intake and nitrogen balance by sheep. Eight castrated male ruminally cannulated sheep (35.0 kg of body weight), Santa Inês x Dorper, in a double 4 × 4 latin square experimental design were used. The experiment lasted 72 d, divided in 4 periods of 8 d of data collection, after 10 d of adaptation. Each animal was fitted with a synthetic leather bag for total feces collection and plastic buckets were used for urine collection. Incubation periods for analysis of in situ degradability corresponded to times 0, 3, 6, 12, 24, 36, 48, 72 and 96 hours. Data were analyzed using procedures of SAS. There was an effect (P <0.05) of hay types on intakes of dry matter (DM), crude protein (CP), ether extract (EE), total digestible nutrients (TDN), non-fiber carbohydrates (NFC) and neutral detergent fiber corrected for ash and protein (NDFap). The intake and apparent digestibility of nutrients was lower (P <0.05) for stylo hay. In vivo DM digestibility of Jiggs (47.6%), Tifton-85 (53.4%), stylo (29.3%) and alfalfa (53.2%) and in situ DM degradability were equivalent in the range from 7.6 to 63.2 hours of degradation. In vivo NDFap digestibility of Jiggs (53.7%), tifton-85 (64.4%), stylo (42.2%) and alfalfa (56.2%) hays and in situ NDFap degradability were equivalent from 37.3 hours. The nitrogen balance was negative only for animals fed stylo hay. The hays provided satisfactory intake and nutrient digestibility for sheep, except stylo hay. Comparisons between in vivo and in situmethods require further research with different forage sources. Supported by Fapemig, CNPq, Capes, and INCT-CA.